The frequent user's decision-making process when contacting urgent and/or emergency services. (30th September 2020) - Worrillow, N; South, J; Cole, A; Collin, S; Briggs, M
Abstract: Background: There is a lack of qualitative research that has been undertaken which has captured the perspective of frequent users to urgent and emergency healthcare services. Previous research has viewed and studied this population largely by using retrospective routine data, which focuses on the patient's demographic, presenting symptom or demand implication. Current research now advocates that these vulnerable and complex individuals are using these services due to their unmet needs or multiple comorbidities. The aim of this research was to explore the patient's decision-making process and their motivations for repeatedly contacting urgent and emergency services. Methods: Semi-structured interviews were undertaken with a small cohort of six previously identified frequent users to urgent and emergency healthcare services. These participants were recruited into the study by a third sector organisation, due to the vulnerabilities and complexities of these individuals' lifestyles. A framework analysis was used to code and extract relevant themes and concepts from the interviews. Results: Social prescribing through a named support worker enables navigation and re-engagement into a range of services that benefits this population and reduces their demand upon other services. The support given through social prescribing organisations can counteract the lack of personal support networks and resilience factors that these individuals experience. In addition, individuals who have been re-referred into substance misuse services should be offered alternative engagement programmes, which differ from their initial programme. Conclusions: Current inequities of outcomes and access to services should be examined, in relation to vulnerable and complex individuals who have reduced support networks and limited resilience factors. Future research should be undertaken regarding the benefits for frequent users of social prescribing to support patient outcomes and re-integration into services. Key messages: Social prescribing is the link that enables complex and vulnerable frequent users to navigate and re-engage into a range of health and social care services. Examining the inequities faced by frequent users to urgent and emergency healthcare services.